Hannah Arendt i sobowtóry. Próba myślenia - Kuczyńska-Koschany, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The essay discusses an issue that has not yet been studied separately: Hannah Arendt and her autobiographical crumbs scattered across other people’s biographies that she wrote and in her own biographies, both literary and cinematic. I called it an attempt at thinking, i.e. a synonym of a (biographical) essay. When Arendt writes about, e. g. Walter Benjamin or Rahel Varnhagen, she also – sometimes – writes about herself. When she smokes a cigarette in a specific way (rather than any other) or speaks German, she creates specific non-verbal doppelganger-like constructions.